ELECTRICAL AND ACOUSTIC PARAMETERS OF LOWER PERMIAN CARBONATE ROCKS (WESTERN PART OF THE HLYNSKO-SOLOKHIVSKYI OF GAS-OIL-BEARING DISTRICT OF THE DNIEPER-DONETS BASIN) - Vyzhva, S.; Onyshchuk, V.; Onyshchuk, I.; Reva, M.; Shabatura, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The main objective of this article is to study electrical parameters of Lower Permian carbonate rocks of Western part of the Hlynsko-Solokhivskyi gas-oil-bearing district of the Dnieper-Donets Basin (DDB) in normal (atmospheric) and modeling (reservoir) conditions. In atmospheric conditions it has been revealed that the resistivity of dry extracted limestones (the specific electrical resistivity of framework of grains was measured) varies from 12.147 kΩ⋅m to 111.953 MΩ⋅m (mean 1.542 MΩ⋅m). The resistivity of saturated limestone samples with kerosene varies from 44.478 kΩ⋅m to 14.449 MΩ⋅m (mean 1.435 MΩ⋅m). The resistivity of dry and saturated with kerosene samples is almost the same. The resistivity of limestones saturated with model of reservoir water (salinity M = 190 g/l) is lower and varies from 1.11 Ω⋅m to 23.16 Ω⋅m (mean 3.12 Ω⋅m). It has been determined that formation resistivity factor of limestones in atmospheric conditions varies from 13.5 to 230 Ω⋅m (mean 32.5 Ω⋅m). In addition to resistivity, the parameter of relative permittivity of investigated limestones was studied. It was determined that relative permittivity of dry limestones varies from 3.0 to 7.5 (mean 4.2). Relative permittivity saturated samples of limestones with kerosene varies from 2.8 to 8.8 (mean 4.5) and practically does not differ from dry ones but significantly lower than values of samples saturated with model of reservoir water (from 655 to 9565, mean 4280). That means when pores of limestones are saturated with NaCl solution their relative permittivity increases rapidly – from hundreds to thousands times (on average 944 times). It can be explained by the high conductivity of model of reservoir water. Limestones saturated with NaCl solution have velocities of P-waves in the range from 3346 m/s to 4388 m/s (mean 4030 m/s), and velocities of Swaves – from 1753 m/s to 2121 m/s (average 1942 m/s). If rocks are saturated with kerosene then velocities have strictly higher values – P-waves from 3433 m/s to 4514 m/s (mean 4011 m/s) and S-waves – from 2137 m/s to 2464 m/s (average 2344 m/s). Physical modelling of reservoir conditions (temperature 50 °С, pressure 30 MPa) showed that the specific electrical resistivity varies from 0.81 Ω⋅m to 13.19 Ω⋅m (mean 2.67 Ω⋅m), and limestones – from 0.49 Ω⋅m to 7.81 Ω⋅m (mean 1.95 Ω⋅m). Also, "specific electrical resistivity – pressure" connection was investigated. Due to the closure of microcracks and the deformation of the pore space, the electrical resistance of rocks increases with increase of pressure. The regression dependence of the formation resistivity enlargement factor with pressure for the studied rocks has a linear character. It was determined that in reservoir conditions the range of the formation resistivity factor for limestones varied from 17.3 to 271.9 Ω⋅m (mean 50.7 Ω⋅m), and range of variation of porosity coefficient was from 0.040 to 0.169 Ω⋅m (mean 0.118 Ω⋅m). The comprehensive analysis of petrophysical data has been resulted in a set of correlation ratios between reservoir, electric and elastic parameters of studied limestones in normal and modeling conditions.